Pedoman Analisis Aksesibilitas Dan Konektivitas Angkutan Pariwisata Kabupaten Banyuwangi - Birahmatika, Lilla anjani; Aulia, Askia Esa; Yacub, Garin; Ahyudanari, Ervina (Jurnal Konstruksi dan Infrastruktur : Teknik Sipil dan Perencanaan, 2025)
Banyuwangi Regency, located in East Java, Indonesia, has rapidly emerged as a leading tourism destination due to its exceptional natural beauty and cultural richness. The increasing number of domestic and international tourist visits requires adequate transport infrastructure to ensure accessibility and connectivity across major destinations. Without a well-functioning transport system, the tourism sector may face barriers to sustainable growth and equitable regional development. Accessibility is defined as the ease with which tourists can reach specific destinations, whereas connectivity reflects the degree of linkage and travel efficiency between those destinations. This study seeks to analyze the performance of the tourism transport system in Banyuwangi by applying the Hansen accessibility model, using both to assess spatial accessibility and inter-destination connectivity. Primary data were collected by measuring the distances between selected tourist destinations (ODTWs) along existing transport routes through Google Maps. Secondary data were obtained from the Banyuwangi Regency Tourism Office, including records of tourist arrival volumes. The results show that accessibility values range from 0.0067 to 0.07, while connectivity values vary between 0.87 and 1.09. These findings reveal significant disparities in transport service distribution and functional integration between routes. The study emphasizes the urgent need for strategic planning and investment in transport systems tailored to the dynamics of tourism flows. Enhancing transport accessibility and connectivity is essential not only to support tourist mobility but also to promote inclusive and sustainable tourism development across the region.